2020
DOI: 10.1021/acs.analchem.0c02507
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-Enhanced Raman Gas Spectroscopy for the Study of Microbial Methanogenesis

Abstract: Microbial methanogenesis is a key biogeochemical process in the carbon cycle that is responsible for 70% of global emissions of the potent greenhouse gas methane (CH4). Further knowledge about microbial methanogenesis is crucial to mitigate emissions, increase climate model accuracy, or advance methanogenic biogas production. The current understanding of the substrate use of methanogenic microbes is limited, especially regarding the methylotrophic pathway. Here, we present fiber-enhanced Raman spectroscopy (FE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 72 publications
0
27
0
Order By: Relevance
“…The LODs of this system were determined as 1.2 ppm for CH 4 , 2.9 ppm for C 2 H 6 , 1.6 ppm for C 2 H 4 , 2.7 ppm for C 2 H 2 , 13.8 ppm for H 2 , and 16.7 ppm for CO with the transmission laser of 150 mW (input excitation laser power was about 200 mW), total gas pressure of 1 bar, and exposure time of 60 s. To demonstrate the ability of our method, we compare our method with state‐of‐the‐art report in the study of FERS system based on HC‐ARF. [ 23 ] We have reached a new record of LODs (CH 4 , C 2 H 6 , C 2 H 4 , and C 2 H 2 ) under the presented experimental conditions. This system can detect gas constituents with different concentrations from trace to pure by setting different acquisition time of spectrum.…”
Section: Discussionmentioning
confidence: 86%
“…The LODs of this system were determined as 1.2 ppm for CH 4 , 2.9 ppm for C 2 H 6 , 1.6 ppm for C 2 H 4 , 2.7 ppm for C 2 H 2 , 13.8 ppm for H 2 , and 16.7 ppm for CO with the transmission laser of 150 mW (input excitation laser power was about 200 mW), total gas pressure of 1 bar, and exposure time of 60 s. To demonstrate the ability of our method, we compare our method with state‐of‐the‐art report in the study of FERS system based on HC‐ARF. [ 23 ] We have reached a new record of LODs (CH 4 , C 2 H 6 , C 2 H 4 , and C 2 H 2 ) under the presented experimental conditions. This system can detect gas constituents with different concentrations from trace to pure by setting different acquisition time of spectrum.…”
Section: Discussionmentioning
confidence: 86%
“…The first demonstration of HC-ARF for use in Raman gas sensing was reported in 2017, [15] highlighting that HC-ARF can potentially provide several advantages for Raman-based gas sensing, including lower fibre attenuation, more than an order of magnitude lower overlap between the guided light and the silica microstructured cladding and larger core sizes (which can reduce gas filling time). More recent work [16] further demonstrated these features and showed a limit of detection of $25 ppm for carbon dioxide gas, with 1.3-W laser power at 3.5-bar gas pressure. All reported works so far use fibre lengths of only a few metres; in HC-PBGFs this is limited by the fibre attenuation, whilst using HC-ARFs there is considerable scope to explore longer fibre lengths.…”
Section: Introductionmentioning
confidence: 91%
“…In 2018, a high peak power mid-infrared Raman laser output was reported based on a nodeless HCARF with a high-performance near-infrared and mid-infrared broad spectrum light guide [63,64], as shown in Figure 10. Knebl et al successfully used HCARF for Raman gas sensing and demonstrated its application in environmental science [41,65]. In addition, the research of measuring Raman scattering spectra by HCARF for trace detection is also being developed further [66].…”
Section: Hollow Core Anti-resonant Fiber (Hcarf)mentioning
confidence: 99%